Impacts of a Near-Peer Urban Ecology Research Mentoring Program on Undergraduate Mentors - Aloisio, Jason M.; Roberts, Su-Jen; Becker-Klein, Rachel; Dunifon, Sarah; Lewis, J. D.; Clark, J. Alan; Munshi-South, Jason; Tingley, Karen (Frontiers in Ecology and Evolution, 2022)
Environmental educators have used guided-inquiry in natural and supportive learning environments for decades, but comparatively little programming and research has focused on experiences in urban environments, including in constructed ecosystems like green roofs, or impacts on older youth and adults. To address this gap, we designed a tiered, near-peer research mentoring program called Project TRUE (Teens Researching Urban Ecology) and used a mixed-methods approach to evaluate impacts on undergraduates serving as research mentors. During the 11-week program, undergraduates conducted independent urban ecology research projects in a variety of New York City green spaces, including green roofs. They mentored a team of high school students working on their research projects, providing support throughout design, data collection, and dissemination. Our results indicate that these types of hands-on experiences can effectively support youth in learning research and mentoring skills and applying them to effectively manage and support high school students. Furthermore, 18 months after participation, mentors reported a sustained influence on their professional development, career paths, and science interest, especially in the context of their appreciation for nature. These results suggest that tiered, near-peer urban ecology research mentoring programs that utilizes urban green spaces, such as green roofs, can be an effective environmental education tool, especially in densely populated urban areas lacking traditional green space.